Why fly the extra mile? Using stress biomarkers to assess wintering habitat quality in migratory shorebirds - Y Aharon-Rotman; Kate Buchanan; NJ Clark; Marcel Klaassen; WA Buttemer (2016)
Migratory birds make decisions about how far to travel based on cost-benefit trade-offs. However, in many cases the net effect of these trade-offs is unclear. We sought to address this question by measuring feather corticosterone (CORTf), leucocyte profile, avian malaria parasite prevalence and estimating fueling rates in three spatially segregated wintering populations of the migratory shorebird ruddy turnstone Arenaria interpres during their stay in the winter habitat. These birds fly from the high-Arctic breeding ground to Australia, but differ in that some decide to end their migration early (Broome, Western Australia), whereas others travel further to either South Australia or Tasmania. We hypothesized that the extra costs in birds migrating greater distances and overwintering in colder climates would be offset by benefits when reaching their destination. This would be evidenced by lower stress biomarkers in populations that travel further, owing to the expected benefits of greater resources and improved vitality. We show that avian malaria prevalence and physiological stress levels were lower in birds flying to South Australia and Tasmania than those overwintering in Broome. Furthermore, our modeling predicts that birds in the southernmost locations enjoy higher fueling rates. Our data are consistent with the interpretation that birds occupying more costly wintering locations in terms of higher migratory flight and thermoregulatory costs are compensated by better feeding conditions and lower blood parasite infections, which facilitates timely and speedy migration back to the breeding ground. These data contribute to our understanding of cost-benefit trade-offs in the decision making underlying migratory behaviour.